A place for vanishing - Fraistat, Ann (New York : Delacorte Press, 2024)
Looking for a fresh start, sixteen-year-old Libby and her family return to her mother's childhood home only to discover that the house's strange beauty may disguise a sinister past.
Ages 14+
Keywords: Haunted houses -- Juvenile fiction; Emotional problems -- Juvenile fiction; Family problems -- Juvenile fiction; Supernatural -- Juvenile fiction; Thrillers (Fiction); Young adult fiction